Mitochondrial Dysfunction in Lysosomal Storage Disorders - de la Mata, Mario (Diseases, 2016)
Lysosomal storage diseases (LSDs) describe a heterogeneous group of rare inherited metabolic disorders that result from the absence or loss of function of lysosomal hydrolases or transporters, resulting in the progressive accumulation of undigested material in lysosomes. The accumulation of substances affects the function of lysosomes and other organelles, resulting in secondary alterations such as impairment of autophagy, mitochondrial dysfunction, inflammation and apoptosis. LSDs frequently involve the central nervous system (CNS), where neuronal dysfunction or loss results in progressive neurodegeneration and premature death. Many LSDs exhibit signs of mitochondrial dysfunction, which include mitochondrial morphological changes, decreased mitochondrial membrane potential (ΔΨm), diminished ATP production and increased generation of reactive oxygen species (ROS). Furthermore, reduced autophagic flux may lead to the persistence of dysfunctional mitochondria. Gaucher disease (GD), the LSD with the highest prevalence, is caused by mutations in the GBA1 gene that results in defective and insufficient activity of the enzyme β-glucocerebrosidase (GCase). Decreased catalytic activity and/or instability of GCase leads to accumulation of glucosylceramide (GlcCer) and glucosylsphingosine (GlcSph) in the lysosomes of macrophage cells and visceral organs. Mitochondrial dysfunction has been reported to occur in numerous cellular and mouse models of GD. The aim of this manuscript is to review the current knowledge and implications of mitochondrial dysfunction in LSDs.